KINERJA PEGAWAI DI KANTOR CAMAT SENGAH TEMILA KABUPATEN LANDAK - Lorensia Nunung E.42008046 (FISIP Universitas Tanjungpura Pontianak, 2012)
AbstractThis writing is intended to know the officer performance at Sexy Area of Governance in Office of Sub-Regency chief of sengah Temila seen from quality, amount, and time accuracy as keyword from performance. This title is lifted by pursuant to problems of officer performance. in this time earn the us know a lot of problem which is concerning officer performance in institution - governance institution do not aside from mount the Subdistrict. So that writer wish to analyse this problem is furthermore.Key word : quality, quantity and time accuuracy